Art in fruits : a collaborative effort in science culture - Baharuddin, Nasir (University Putra Malaysia, 2012)
In the biological culture of natural science, fruits are considered a most interesting object in which to synthesize an artistic visualization of representation. It gives an interesting form of visual structures and pattern of textures to create into artistic production. Fruit arts are a kind of surreal post-modern creation. Perhaps, in a certain society it becomes a culture and can exist by itself. Its goal will be to cultivate a positive feedback loop, in which works of art lead to new scientific experiments, which lead to new works of art and so on. It helps people to understand that art can actually be found in daily life and be part of culture orientation.